The Role of Teachers as Motivators in Shaping Discipline in Completing Tasks for Special Needs Students at SDN 1 Gunung Sari - Maritza Putri Nadia; Iqoh Sobirotus Solekha; Reza Adi Pangestu (JEES: Journal of Education and Educational Sciences, 2024)
This study analyzes the role of teachers as motivators in forming disciplined characters in children with special needs in grade 4 of SDN 1 Gunung Sari Dalam. With a descriptive qualitative approach, data were collected through observations of teacher-student interactions and interviews. The results showed that teachers provided relief from assignments; for example, regular students got 10 questions, while students with special needs only got 3 questions with guidance. The students with special needs studied had characteristics such as ADHD and speech delays, so they needed a special approach. Teachers acted as directors and motivators, creating an inclusive learning environment, giving praise, and setting realistic goals according to students' interests. The role of parents is very important, with their active involvement strengthening children's emotional development. This study shows that the role of teachers is effective in building discipline in students with special needs, contributing to inclusive education.